2005
DOI: 10.1002/jmri.20283
|View full text |Cite
|
Sign up to set email alerts
|

Differential uptake of ferumoxtran‐10 and ferumoxytol, ultrasmall superparamagnetic iron oxide contrast agents in rabbit: Critical determinants of atherosclerotic plaque labeling

Abstract: Purpose:To compare atherosclerotic plaque uptake of a first (ferumoxtran-10) and second generation (ferumoxytol) ultrasmall superparamagnetic iron oxide (USPIO) contrast agent with different pharmacokinetic/pharmacodynamic properties. Materials and Methods:New Zealand White rabbits maintained on a high cholesterol/fat diet were subjected to balloon injury to the abdominal aorta. Ferumoxtran-10 or ferumoxytol (500 mol/kg) was administered at 2, 4, and 8 weeks following injury. In vivo magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 17 publications
6
101
0
1
Order By: Relevance
“…That the untargeted Gd-mixed micelles are able to penetrate the plaque may be important. Studies involving iron oxide particles have indicated that the uptake of the particles by plaque macrophages is limited by the ability of the particles to diffuse through the abnormal dysfunctional endothelium (23). As a result, the enhancement observed by the targeted micelles is most likely due to both the ability of the material to penetrate the plaque and the specific retention of the material due to macrophage targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the untargeted Gd-mixed micelles are able to penetrate the plaque may be important. Studies involving iron oxide particles have indicated that the uptake of the particles by plaque macrophages is limited by the ability of the particles to diffuse through the abnormal dysfunctional endothelium (23). As a result, the enhancement observed by the targeted micelles is most likely due to both the ability of the material to penetrate the plaque and the specific retention of the material due to macrophage targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, iron oxide particles have been used for imaging of atherosclerosis (27). However, there are factors that limit the clinical application of this approach: (i) iron oxide particles induce signal loss, making differentiation between iron-laden macrophages and imaging artifacts challenging (28); (ii) because of the limited penetration in the plaque, high doses (several times the clinical dose) and long delay times (up to 5 days postinjection) are required (23,27); and (iii) finally, the uptake of iron oxide particles seems to be nonspecific, which may limit their use for plaque imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Such results need to be corroborated with ferumoxytol; however, it seems most likely that this agent also is avidly taken up into atherosclerotic lesions of humans. However, differences between ferumoxytol and ferumoxtran-10 with respect to their clearing from the blood pool, and consequently their various exposure periods to cells with macrophage activity in atherosclerotic plaque, also have to be considered when comparing these agents (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous USPIO accumulation studies have used macrophages treated with USPIO in concentrations ranging from 50 to 500 mg Fe/mL and for time periods lasting from 1 to 72 h (14)(15)(16)(17). On the basis of our preliminary study findings, macrophages were incubated with USPIO (400 mg Fe/mL) for the last 16 h of the 2-d treatment with polarizing stimulus at 37°C in 5% CO 2 (Fig.…”
Section: Uspio Accumulation In M1 and M2 Macrophagesmentioning
confidence: 99%